The Letters and the Law : Legal and Literary Culture in Late Imperial Russia - Schur, Anna (Book collections on Project MUSE., 2022)
"Nineteenth-century Russian literature abounds in negative images of lawyers and the law. The Letters and the Law is the first book to frame the conflict between writers and lawyers as a competition for cultural authority"--